Grassroots Participatory Budgeting Process in Negros Province - Fatima del Prado; Maureen Ane D. Rosellon; Gabriel Antonio Florendo (Philippine Institute for Development Studies (PIDS), 2015)
This paper is a narrative account and assessment of the grassroots participatory budgeting (GPB) process in three municipalities of the Negros Province, namely, Sagay City, Hinigaran, and Cauayan. The GPB process was implemented with the objective of empowering civil society organizations (CSOs) to engage with local government and national government agencies in local development planning. This study is a rapid assessment of the GPB process and involved interviews and focus group discussions with key stakeholders from the local government and civil society, and collection of relevant documents to examine how the GPB FY2015 planning process and prioritization of projects were implemented on the ground on the aspects of CSO participation, LGU-CSO engagement, and integration of GPB process in the local planning process; and to identify bottlenecks in the implementation of subprojects identified in FY2013 and FY2014 GPB process. The paper also provided some insights on areas for further improvement in the subsequent rounds.
Keywords: 330; Philippines; local governance; grassroots; hacked by Kedaong Injection don; participatory planning; bottom-up budgeting (BUB); Negros Occidental; poverty alleviation; civil society organizations (CSOs); budget reform